2012
DOI: 10.1103/physrevb.86.205308
|View full text |Cite
|
Sign up to set email alerts
|

Optical control of entangled states in semiconductor quantum wells

Abstract: We present theory and calculations for coherent high-fidelity quantum control of many-particle states in semiconductor quantum wells. We show that coupling a two-electron double quantum dot to a terahertz optical source enables targeted excitations that are one to two orders of magnitude faster and significantly more accurate than those obtained with electric gates. The optical fields subject to physical constraints are obtained through quantum optimal control theory that we apply in conjunction with the numer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The behavior of electric charge in DQDs has recently been the subject of several theoretical studies proposing schemes to coherently control the dynamics of the electrons [12][13][14][15][16][17] . Theoretical strategies based on global gate voltages 14,15 and optimized laser pulses 16,17 have shown that it is possible to control the electronic states in DQD models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of electric charge in DQDs has recently been the subject of several theoretical studies proposing schemes to coherently control the dynamics of the electrons [12][13][14][15][16][17] . Theoretical strategies based on global gate voltages 14,15 and optimized laser pulses 16,17 have shown that it is possible to control the electronic states in DQD models.…”
mentioning
confidence: 99%
“…Theoretical strategies based on global gate voltages 14,15 and optimized laser pulses 16,17 have shown that it is possible to control the electronic states in DQD models. However, the fabrication of working devices would be easier if coupling to terahertz optical fields 17 or the use of strong gate voltages modulated in picosecond time-scales 14,15 was avoided. In this communication, we demonstrate an optimized method to control the single-electron dynamics in DQDs by applying local gate voltages.…”
mentioning
confidence: 99%
“…In addition, quantum computation theoretically requires extremely high fidelity in the elementary quantum state transformations. Optical control of quantum dot based devices is of fundamental interest for a wide range of applications in quantum information [35,36,37,38,39,40]. For example, optical manipulation is an alternative in order to store qubits in the electron spin [35].…”
Section: Introductionmentioning
confidence: 99%
“…These various control strategies include the use of analytically wellestablished phenomena like the paradigmatic LandauZener (LZ) transition [12][13][14], Landau-Zener-Stückelberg interferometry [15,16], the composite pulse (CP) protocol and several other two-level control strategies [12,[24][25][26][27], and OCT [18][19][20][21][22][23]. For the experimental control strategies, as can be seen in [10,[15][16][17], the first stage is the measurement of the charge stability diagram (CSD).…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal Letter of Grossmann et al [8] a number of theoretical and experimental works have addressed the issue of controlling the localization of an electron state in a double well potential [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. These various control strategies include the use of analytically wellestablished phenomena like the paradigmatic LandauZener (LZ) transition [12][13][14], Landau-Zener-Stückelberg interferometry [15,16], the composite pulse (CP) protocol and several other two-level control strategies [12,[24][25][26][27], and OCT [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%